MENINGKATKAN MINAT BELAJAR SISWA KELAS IV MELALUI MEDIA GAME ONLINE WORDWALL PADA MATA PELAJARAN PPKN - Erlynda Runtut Bela Vista; Fida Chasanatun; Kustini Kustini (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2023)
The learning interests of SD Negeri 1 Bendoagung students varied, but when seen from the observations, most students were not very interested in the learning process. This problem occurs because there is a lack of use of interesting learning media and makes students happy. The purpose of this study is to prove whether the online game media Wordwall can increase students' interest in learning. The type of research used is Classroom Action Research (CAR). This study involved 13 students. The methods used were direct observation, questionnaires, and documentation used to collect data. The results showed that in the first cycle the interest in learning in the very good category was only 38.46%, so that students who got in the good category reached 61.53%. In cycle II, students' interest in learning increased to 23.08%, students who were very good became 84.61% and students who were good decreased to 15.38%. This data shows that wordwall is an online game media that is able to increase students' interest in PPKN subjects at SD Negeri 1 Bendoagung.